Позитронна спектроскопія високотемпературних надпровідників YBa2Cu3O7-δ, опромінених малими флюенсами швидких нейтронів - Gorelov, B. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
The intensive subthreshold defect formation occurs in the intermediate layers of YBa2Cu3O7-δ (δ ≈ 0) high temperature superconductor under neutron irradiation with low fluencies of 1011 < ф ≤1014 сm-2. The number of defects created due to the low energy mechanism more than 103 times exceeds the content of radiation defects formed owing to the impact mechanism. The subthreshold defect formation reveals in a decrease of the electron density in the intermediate layers with nonmonotone lowering concentration of vacancy clusters. The behavior of electron density is caused by formation of Ва and Cu1 cation defects and their accumulation in the thin surface layer of crystals. It is supposed that the subthreshold defect formation is related to the decay of collective excitations stimulated in the non equilibrium state of electron density under the neutron irradiation.